Eastern Caribbean : a guide to the people, politics, and culture - Ferguson, James, 1956- (In focus (London, England), 1997)
A guide to the history, culture, economy, and society of the Eastern Caribbean Islands, including Martinique, Saint Lucia, Barbados, and Guadeloupe.